Far‐field connectivity of the UK's four largest marine protected areas: Four of a kind?. Issue 5 (17th May 2017) - Robinson, J.; New, A. L.; Popova, E. E.; Srokosz, M. A.; Yool, A.
Abstract: Marine Protected Areas (MPAs) are established to conserve important ecosystems and protect marine species threatened in the wider ocean. However, even MPAs in remote areas are not wholly isolated from anthropogenic impacts. "Upstream" activities, possibly thousands of kilometers away, can influence MPAs through ocean currents that determine their connectivity. Persistent pollutants, such as plastics, can be transported from neighboring shelf regions to MPAs, or an ecosystem may be affected if larval dispersal is reduced from a seemingly remote upstream area. Thus, improved understanding of exactly where upstream is, and on what timescale it is connected, is important for protecting and monitoring MPAs. Here, we use a high‐resolution (1/12°) ocean general circulation model and Lagrangian particle tracking to diagnose the connectivity of four of the UK's largest MPAs: Pitcairn; South Georgia and Sandwich Islands; Ascension; and the British Indian Ocean Territory (BIOT). We introduce the idea of a circulation "connectivity footprint", by which MPAs are connected to upstream areas. Annual connectivity footprints were calculated for the four MPAs, taking into account seasonal and inter‐annual variability. These footprints showed that, on annual timescales, Pitcairn was not connected with land, whereas there was increasing connectivity for waters reaching South Georgia, Ascension, and, especially, BIOT. BIOT also had a high degree of both seasonal and inter‐annual variability, which drastically changed its footprint, year‐to‐year. We advocate that such connectivity footprints are an inherent property of all MPAs, and need to be considered when MPAs are first proposed or their viability as refuges evaluated. Key Points: Marine protected areas (MPAs), set up to protect endangered species, are vulnerable to upstream impacts from land due to ocean circulation Particle‐tracking simulations show the land connectivity of four major British MPAs and give a "connectivity footprint" at annual timescales Connectivity to land differs substantially between MPAs with strong seasonal/inter‐annual variability showing the utility of the footprints Plain Language Summary: Marine Protected Areas (MPAs) are typically established to conserve important ecosystems and protect marine species. However, even remote MPAs are not wholly isolated from impacts elsewhere, and can be connected via energetic ocean currents to impacts in "upstream areas" hundreds or even thousands of kilometres away. For instance, separate populations of marine species can be connected through larval dispersal by ocean currents, such that negative ecosystem impacts—overfishing or pollution—in a seemingly remote location may drastically affect a MPA. Here, we present "connectivity footprints" of four UK MPAs using a Lagrangian particle‐tracking technique within a high‐resolution ocean model, and evaluate their connectivity with land. At the 1‐year timescale, Pitcairn is essentially unconnected with land, whereas the South Georgia, Ascension and BIOT MPAs are increasingly connected with remote land, with variability (seasonal and interannual) notably high for BIOT. In terms of exposure to pollution, we also consider the population density of connected coastlines, and identify this as an important risk factor in the management of MPAs. We advocate connectivity footprints of MPAs as a tool to improve future MPA designation, and in spatial planning of current MPA networks, and we suggest future work to better diagnose connectivity of MPAs.